Elaboración y aplicación de un manual lúdico para mejorar la enseñanza de la lógica matemática en los niños y niñas de 5 años de la escuela pedro Vicente Maldonado, cantón Pujilí, provincia de Cotopaxi en el período 2012-2013 - Molina Espín, Ginna Alexandra (2013)
This researching was conducted with appropriate methods and following to the structure provided by the institution, it permits to analyze the theoretical and conceptual foundation of mathematical logic in teaching children, taking account the problems of teaching mathematical logic in “ Pedro Vicente Maldonado school and using a manual to improve the teaching playful mathematical logic. This researching will help children have strong knowledge of mathematical logic and develop their intelligence, this project has a descriptive researching techniques based on surveys, observation and interviews to authorities, teachers and parents, for developing the playful manual. The student is the most important in class, and this researching will benefit them because they will gain knowledge and teachers should be trained for a better development when giving their classes and there are no failures at the end of the school year. Also we could arrange the delivery of the manual playful mathematical logic that was the proposal; it was recepted in a good way so we conclude this.